Aflatoxinas em cervejas artesanais: uma abordagem preditiva da produção durante a malteação de trigo - Schabo, Danieli Cristina (2020)
Aspergillus and Penicillium species were isolated from 40 samples of malted/unmalted cereals used in the artisanal beers production and characterized for their toxigenic potential. A. flavus, producer of AFs was selected for malting wheat using standard conditions (steeping degree 45%, germination at 14.5±0.5°C and 95-98% relative humidity and drying for 16h at 50°C, 1h at 60°C, 1h at 70°C and 5h at 80°C) for checking AFs in 11 steps. The same isolate was inoculated in wheat for malting under different steeping degree conditions (41-47%), germination temperature (13-19°C) and time (48-120h) to verify the AFs production in the malt according to these conditions. The prevalence and concentration of mycotoxins in beers consumed worldwide was assessed through a systematic review followed by meta-analysis. Aspergillus section Nigri uniseriate (n=1) and A. flavus (n=1) were isolated from wheat and Aspergillus section Nigri uniseriate (n=1) was isolated from wheat malt. Penicillium sp. (n=2), P. citrinum (n=5), A. section Nigri uniseriate (n=2) and bisiseriate (n=1) and A. tamarii (n=1) were isolated from barley malt. All P. citrinum isolates were characterized as citrinin producers and A. flavus as producer of AFB1 and AFB2. During malting under standard conditions, AFB1 and AFB2 were produced in concentrations of 229.35-455.66 μg/g and 5.65- 13.05 μg/kg, respectively. Only AFB2 increased during steeping, while only AFB1 decreased during germination. AFB1 and AFB2 decreased at the end of drying (80°C). At the end of the malting, levels of 240.46 μg/kg AFB1 and 6.36 μg/kg AFB2 remained in the malt. When different conditions were tested, the AFs were produced in all conditions tested, with AFB1 at levels between 15.78±3.54 µg/kg (41%ST, 13°C, 48h) and 284.66±44.34 µg/kg (47%ST, 19°C, 120h). The data were transformed and adjusted to a linear regression that explained 84% of the results. According to the model obtained [sqrt (AFB1) = ̶4.799002 + 0.371135T + 0.100009t], AFB1 increased with increasing germination temperature or time. The steeping degree had no effect on the AFB1 levels of the malt. The meta-analysis of 6,030 beer samples, showed that the worldwide prevalence of mycotoxins in beers is 31% (95% CI=27-35%; I 2=91%, p=0) and higher prevalence in European countries [46% (95% CI=40-52%)]. Ochratoxin A (56%), fumonisins (54%) and deoxynivalenol (46%) are prevalent and AFs are present in 11% of the world's beers already tested. The average concentration of mycotoxins in beers is 10.17 µg/L (95% CI=8.16-12.67 µg/L; I2=100%, p=0). The highest concentrations ever recorded were in the countries of Africa 73.95 µg/L (95% CI = 46.27-118.20 µg/L) and comprised deoxynivalenol [2.94 µg/L (95% CI=14.20-51.14 µg/L)], AFs [25.28 µg/L (95% CI=10.17-62.82 µg/L)] and fumonisins [23.19 µg/L (95% CI=15.66-34.34 µg/L]. The production of AFs occurred during the steeping of grains; however, it was influenced by the temperature and time of germination of grains. The occurrence of mycotoxins in beers shows the need for regulatory limits, especially in artisanal beers.